Ethnobotany of Canarium plant species used by Tobelo Dalam - M. NASIR TAMALENE; MIMIEN HENIE IRAWAT AL MUHDHAR; ENDANG SUARSINI; FATCHUR RAHMAN; SAID HASAN (Society for Indonesian Biodiversity, 2016)
Tamalene MN, Al-Muhdhar MHI, Suarsini E, Rahman F, Hasan S. 2016. Ethnobotany of Canarium plant species used byÂ Tobelo Dalam (Togutil)Â ethnic community of Halmahera Island, Indonesia. Biodiversitas 17: 61-69. Tobelo Dalam (Togutil) ethnic group has been using local plants for years; one of them is Canarium. The ethnic are nomads and live in conservation forests. Data on ethnobotanical knowledge was collected through interview technique with â€œwork in the woodâ€ method. There were three types of informant: main informants, key informants, and recommended informants. Main informants were chosen through purposive sampling technique while key informants and recommended informants were chosen through snowball sampling technique. The informants in this study were grouped based on their age: 14 children (5-11 years)Â 13 adults (26-45 years), nine (46-65 years) and three old age (â‰¥ 65 years).Â The result of fidelity level analysis (FL%) indicated that all age groups had FL value of 100% in utilizing walnut as local food. Regarding the use of skin exocarp the result was as follow: children (FL: 28.57%),Â teenagers (FL: 77,77%), adults (FL: 69,23%), and elder and old age (FL: 100%).Â Whereas, the use of Shell endocarp among the age groups was as follow: children (FL: 14.28%),Â teenagers (FL: 66.66%), adults (FL: 46,15%), elder (FL: 33.33%), and old age (FL: 100%).Â CanariumÂ bark had value of FL% in children (FL: 35,71%),Â teenagers (FL: 61.11%),Â adults (FL: 92.3%),Â elder (FL: 33.33%), andÂ old age (FL: 100%).Â The use of resin by the groups was children (FL: 50%),Â teenagers (FL: 83.33%),Â adults (FL: 92.3%),Â elder and old age (FL: 100%).Â The use of Canarium root among the groups was children (FL: 14.28%),Â teenagers (FL: 61.11%),Â adults (FL: 92.3%),Â elder (FL:Â 33.33%),Â Â and old age (FL: 100%).Â The use of plantâ€™s trunk was as follow: children (FL: 50%),Â teenagers (FL: 77.77%), adults, elder, and old age (FL: 100%).Â The research indicated that walnut had high utility value. All parts of the plant (root, wood, bark, and resin)Â were exploited for economic, health and cultural interest.